Estudo numérico e experimental do comportamento de painéis duplos treliçados preenchidos com concreto moldado no local - Lacerda, Benício de Morais (2013)
In front of a large growth scenario in the civil construction industry, new constructive processes are being used for construction of small and medium size structures, as is the case of systems formed by double precast concrete panels lattice filled with concrete cast in place. This study aimed to investigate experimentally and numerically, the factors that affected the shear strength on the interface between concrete cast at different ages. The models were subjected to a direct shear and shear in bending. In experimental program was tested 26 models subject to a direct shear taking into account different widths of concrete filling as 7 cm, 9 cm and 13 cm, with smooth and rough interfaces, as well as different the concrete of compressive strength. Also were tested two beams with 3 m of span under shear in bending. In numerical modeling were used finite solids elements, bar elements and contact elements with physical nonlinear analysis. The models results under direct shear showed that the reinforcement amount which crosses the interface, the concrete compressive strength, the interface surface and a lowest ratio between the widths of the filling region of concrete and precast concrete improves the behavior of the structural element. In general, the models with smooth interface slided in the order of 10-2 mm while the rough surfaces models were in the order of 10-3 mm. Numerically, there was a gain in the shear strength of 36,61% by increasing the compressive strength of the filling concrete region\'s of 20 MPa to 28,4 MPa for smooth interface models. The models with truss and without stirrups resisted 71% of the breaking strength of models with all reinforcement. This rate dropped to 40% for the models with stirrups and without truss connection. The beams under shear in bending behaved as the monolithic models without sliding interface and presented cracks distributed in the region of concentrations of the stirrups under large deformations.